Typological variation in the expression of Evidentiality - Aghamalıyeva, Aysel (International Journal of Language and Literary Studies, 2025)
This article examines evidentiality as a complex and debated concept in linguistics. While scholars disagree on whether evidentiality is a grammatical or lexical category, there is consensus that its core function is to indicate the source of information. It answers epistemological questions such as: Was the event directly witnessed? Was it inferred from evidence? Was it learned through hearsay or reports? The article analyzes how evidentiality is expressed in Azerbaijani, English, and Spanish, focusing on both grammatical and lexical strategies. By comparing these languages, the study reveals typological differences and highlights the role of evidentiality in communication. It also discusses the relationship between evidentiality and epistemic modality, showing how both influence the speaker’s stance and interpretation of truth.